2019
DOI: 10.21608/ebwhj.2019.33474
|View full text |Cite
|
Sign up to set email alerts
|

Addition of intrathecal dexamethasone to bupivacaine for spinal anesthesia in cesarean section

Abstract: Background: Post-caesarean section pain is an important issue in obstetrics. Several studies have shown the importance of adequate postoperative analgesia on mobilization, rehabilitation and decreasing the length of hospital stay. Large amounts of opioid analgesic drugs are often required in the management of intense post-operative pain. However, this option is associated with many side effects. Objective: The aim of the study was to assess the efficacy of adding dexamethasone to bupivacaine for spinal anesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Dexamethasone was nearly as effective fentanyl in reducing incidence and severity of shoulder pain and facilitating ovarian cystectomy under spinal anesthesia. Antinociceptive effects of dexamethasone could be explained by its neuro-antiinflammatory effects and its ability to prevent C fiber mediated nociception and blocking ectopic neuronal firing [11]. Furthermore, analgesic effects of intrathecal dexamethasone might be related to its ability to regulate the nuclear factor-kB at the spinal cord which is responsible for "central sensitization" inhibition [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Dexamethasone was nearly as effective fentanyl in reducing incidence and severity of shoulder pain and facilitating ovarian cystectomy under spinal anesthesia. Antinociceptive effects of dexamethasone could be explained by its neuro-antiinflammatory effects and its ability to prevent C fiber mediated nociception and blocking ectopic neuronal firing [11]. Furthermore, analgesic effects of intrathecal dexamethasone might be related to its ability to regulate the nuclear factor-kB at the spinal cord which is responsible for "central sensitization" inhibition [21].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dexamethasone inhibits peripheral as well as central prostaglandin synthesis at the level of the spinal cord, minimizing the sensitization of both the inflammatory and the pain pathways [22]. Intrathecal use of both dexamethasone and fentanyle remains off label, however previous trials demonstrated that no serious complications were recorded from the intrathecal use of both drug [9], [23], [24], [25], [26], [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intrathecal administration of dexamethasone prolongs the duration of sensory block [ 12 , 13 ]. However, the effect of intravenous dexamethasone on the duration of spinal anesthesia has been assessed by a few studies with conflicting results [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%